Thrust Characteristics of Ducted Propeller and Hydrodynamics of an Underwater Vehicle in Control Motions - Jiaming Wu; Yizhe Dou; Haiyan Lv; Chenghua Ma; Le Zhong; Shunyuan Xu; Xiangxi Han (Journal of Marine Science and Engineering, 2021)
A numerical technique to simulate the hydrodynamic behavior of ducted propellers attached to an underwater vehicle traveling under the mutually interacting flow fields of the vehicle and the propellers is proposed; the hydrodynamic performance of the propellers and the hydrodynamic loading on the main body of the vehicle when it is in different kinds of motion is investigated numerically. In the research, 3D geometric models of the duct, propeller, and main body of the vehicle are first constructed according to their geometrical features. A computational fluid dynamics (CFD) technique based on the hybrid algorithm of dynamic mesh-nested sliding mesh is applied to solve the Navier–Stokes equations that govern the fluid motion around the duct, propeller, and main body of the vehicle when it is in motion. These equations are solved numerically with the CFD code Fluent. With the proposed numerical simulation technique, the hydrodynamic characteristics of the thrusts generated by the ducted propellers and the loading on the main body in the vehicle system under the mutually interacting flow fields are observed. The results of our numerical simulation indicate that the hybrid algorithm of dynamic mesh-nested sliding mesh can simulate multiple degrees of freedom of motion in underwater vehicle systems. In different motion states, the main body exerts a significant influence on the investigated flow fields; during the vehicle motions, negative wakes are formed on both sides of the main body, which lead to a decrease in the thrusts generated by the propellers on both sides. The thrust of the middle propeller is greater than that of the normal single one because of the obstructing effect in the tunnel caused by the main body.